Potensi Wisata Kuliner dan Motivasi Wisatawan di Kota Depok Jawa Barat Tahun 2019 - Ardi Mularsari (Populis : Jurnal Sosial dan Humaniora, 2022)
The development of culinary tourism in the city of Depok, West Java Province needs to be appreciated. The Central Statistics Agency (BPS) noted that in 2012 Depok City's economic growth reached 7.1%. This figure far exceeds economic growth in West Java at 6.2%. Individual service businesses in Depok have also contributed to the economic growth rate of around 10.56 percent. Services that support the economy of Depok include laundry services, motorbike services, salons and private tutors. These businesses are in the midst of community settlements, especially culinary efforts. The study of culinary tourism potential  in the city of Depok, West Java Province is expected to be a contribution of constructive thoughts and input on the development of culinary tourism as one of the mainstay tourism of Depok city. Perkembangan wisata kuliner di kota Depok, Propinsi Jawa Barat perlu diapresiasi. Badan Pusat Statistik (BPS) mencatat pada 2012 pertumbuhan perekonomian Kota Depok mencapai 7,1%. Angka tersebut jauh melebihi pertumbuhan ekonomi di Jawa Barat sebesar 6,2%. Usaha jasa perorangan di Depok turut mendorong laju pertumbuhan ekonomi sekitar 10,56 persen. Layanan jasa yang menyokong perekonomian Depok antara lain dari jasa pencucian baju (laundry), servis motor, salon dan guru privat. Usaha-usaha itu berada di tengah-tengah pemukiman masyarakat, khususnya usaha kuliner. Studi potensi wisata kuliner  wisatawan  di kota Depok Provinsi Jawa barat diharapkan akan menjadi sumbangan pemikiran dan masukan konstruktif pada perkembangan wisata kuliner sebagai salah satu wisata andalan kota Depok.